Paternal Post-Natal Depression (PPD): Simptom Dan Faktor Penyebabnya - Kurniasari Pratiwi; Endang Khoirunnisa (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Mental health status affects men and women of all ages, races, socioeconomics. Mental health conditions can cause changes in thoughts, feelings, moods, behavior and affect a person's ability to function every day and in relationshipswith other people. Perinatal depression is a mental health condition including major or minor depressive episodes that occur during pregnancy or in the first twelve months after delivery. Perinatal depression is the most common medical complication ofpregnancy. The focus of world attention has begun to realize the importance of paying attention to women's mental health status, but unfortunately attention to Paternal PostNatal Depression (PPD) is still lacking.Methode: The aim of this research is to review current research on postnatal depression in fathers regarding symptoms and causal factors. This research carried out a comprehensive search of 5 databases from 2018 - 2023. Initial searchparameters with keywords: